Cantón Mayo, I. y Tardif, M. (Coords.) (2018). Identidad profesional docente - Robinson Seisdedos, María¡ Soledad (Revista Educación, Política y Sociedad, 2018)
Cantón Mayo, I. y Tardif, M. (Coords.) (2018). Identidad profesional docente. Madrid: Narcea, 229 pp.